Protopine/Gemcitabine Combination Induces Cytotoxic or Cytoprotective Effects in Cell Type-Specific and Dose-Dependent Manner on Human Cancer and Normal Cells - Mercedes Garcia-Gil; Benedetta Turri; Morena Gabriele; Laura Pucci; Alessandro Agnarelli; Michele Lai; Giulia Freer; Mauro Pistello; Robert Vignali; Renata Batistoni; Silvia Marracci (MDPI AG, 2021)
The natural alkaloid protopine (PRO) exhibits pharmacological properties including anticancer activity. We investigated the effects of PRO, alone and in combination with the chemotherapeutic gemcitabine (GEM), on human tumor cell lines and non-tumor human dermal fibroblasts (HDFs). We found that treatments with different PRO/GEM combinations were cytotoxic or cytoprotective, depending on concentration and cell type. PRO/GEM decreased viability in pancreatic cancer MIA PaCa-2 and PANC-1 cells, while it rescued the GEM-induced viability decline in HDFs and in tumor MCF-7 cells. Moreover, PRO/GEM decreased G1, S and G2/M phases, concomitantly with an increase of subG1 phase in MIA PaCa-2 and PANC-1 cells. Differently, PRO/GEM restored the normal progression of the cell cycle, altered by GEM, and decreased cell death in HDFs. PRO alone increased mitochondrial reactive oxygen species (ROS) in MIA PaCa-2, PANC-1 cells and HDFs, while PRO/GEM increased both intracellular and mitochondrial ROS in the three cell lines. These results indicate that specific combinations of PRO/GEM may be used to induce cytotoxic effects in pancreatic tumor MIA PaCa-2 and PANC-1 cells, but have cytoprotective or no effects in HDFs.